Effective Removal of Sulfanilic Acid From Water Using a Low-Pressure Electrochemical RuO2-TiO2@Ti/PVDF Composite Membrane - Zheng, Junjian; Yan, Kaili; Wu, Zhichao; Liu, Mingxian; Wang, Zhiwei (Frontiers in Chemistry, 2018)
Removal of sulfanilic acid (SA) from water is an urgent but still challenging task. Herein, we developed a low pressure electrochemical membrane filtration (EMF) system for SA decontamination using RuO2-TiO2@Ti/PVDF composite membrane to serve as not only a filter but also an anode. Results showed that efficient removal of SA was achieved in this EMF system. At a charging voltage of 1.5 V and a electrolyte concentration of 15 mM, flow-through operation with a hydraulic retention time (HRT) of 2 h led to a high SA removal efficiency (80.4%), as expected from the improved contact reaction of this compound with ROS present at the anode surface. Cyclic voltammetry (CV) analysis indicated that the direct anodic oxidation played a minor role in SA degradation. Electron spin resonance (ESR) spectra demonstrated the production of •OH in the EMF system. Compared to the cathodic polarization, anodic generated ROS was more likely responsible for SA removal. Scavenging tests suggested that adsorbed •OH on the anode (>•OH) played a dominant role in SA degradation, while O2•− was an important intermediate oxidant which mediated the production of •OH. The calculated mineralization current efficiency (MCE) of the flow-through operated system 29.3% with this value much higher than that of the flow-by mode (5.1%). As a consequence, flow-through operation contributed to efficient oxidation of SA towards CO2 and nontoxic carboxylic acids accounting for 71.2% of initial C. These results demonstrate the potential of the EMF system to be used as an effective technology for water decontamination.